HASIL DAN MUTU JAGUNG MANIS (ZEA MAYS SACCHARATA STURT) DENGAN PERLAKUAN PUPUK KANDANG AYAM DAN KALIUM - N, Muhammad Yusuf (Faculty of Agriculture, Universitas Malikussaleh, 2018)
The aim of this research was to know the effect of chicken manure and potassium on the yield and quality of sweet corn. The research used a Randomized Block Design Factorial with 2 factors and 3 replications. The first factor is chicken manure: A0 (0 Kg/ha), A1 (10 Kg/ha), A2 (15 Kg/ha) and A3 (20 Kg/ha). The second one is potassium fertilizer: K0 (0 Kg K2O/ha), K1 (90 Kg K2O/ha),K2 (120 Kg K2O/ha), and K3 (150 Kg K2O/ha). The result research showed a not significant increased in the yield and quality of sweet corn. The combination of treatment A0K2 gave the best yield and quality.